Magnetization and Temperature Dependence of the Mossbauer Spectrum Shift for an Insulator. - COEY, JOHN MICHAEL DAVID (American Physical Society, 1969)
The results of a Mossbauer-effect study of HoFeO3 in the temperature range 99-875?K are presented. Special attention is paid to the shift of the center of the spectrum and its temperature dependence both above and below the Neel point TN. Although no discontinuity is found at the Neel temperature, the total shift has a different temperature dependence for T<TN and for T>TN. The experimental results are compared with theoretical predictions based on a magnetization-dependent Debye model. Also, a theoretical model based on the supertransferred process is presented which gives rise to a magnetization-dependent isomer shift, although the calculated effect is almost two orders of magnitude too small.
PUBLISHED
Keywords: Physics